TRAINING MONITORING WITHOUT TECHNOLOGY: FACTS OR FICTION? - Cuzzolin, Francesco (Sport- és Egészségtudományi füzetek, 2025)
In this presentation, I address the complexities and practi-calities of implementing effective monitoring procedures in athletic training, with a specific focus on basketball, without relying on costly technological solutions. Based on my extensive experience in high-performance basketball environment, I intend to equip coaches and prac-titioners with executable insights and methodologies to en-hance athlete development and performance. The presentation begins by acknowledging the common be-lief among students and practitioners that effective training monitoring requires massive investments in technology, making it out of reach to those with limited resources. I challenge this notion by advocating for a proactive and re-sourceful approach to training monitoring.